Penerapan Model Kooperatif Tipe Numbered Head Tgether Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMP - Adi Adi; Samsul Arifin; Bobbi Rahman (IndoMath: Indonesia Mathematics Education, 2019)
Mathematical communication skills are abilities that must be possessed by students in learning mathematics so that students can convey ideas or ideas both verbally and in writing. Based on the results of observations made at SMP Muhammadiyah 5 Kota Tangerang, students' mathematical communication skills are still low. Responding to these problems, teachers need to apply cooperative learning models. One type of cooperative learning model that can train students' mathematical communication skills is Numbered Head Together (NHT). The purpose of this study is to investigate the improvement in mathematical communication skills of students who get Numbered Head Together (NHT) learning higher than students who get conventional learning. This study uses a quasi experimental design type nonequivalent control group design. The population in this study were 4 grade VIII students of SMP Muhammadiyah 5 Kota Tangerang and the sample of this study were students of grades VIII.2 and VIII.3. The sampling technique uses cluster random sampling. The research hypothesis was tested with a nonparametric test, namely Mann Whitney because the sample in this study amounted to 38 students from two classes VIII.2 and class VIII.3. The results showed that the increase in mathematical communication skills of students who obtained mathematics learning with the Numbered Head Together (NHT) model was higher than students who obtained conventional learning.